2008
DOI: 10.1001/archpediatrics.2007.38
|View full text |Cite
|
Sign up to set email alerts
|

Emerging New Clinical Patterns in the Presentation of Celiac Disease

Abstract: To evaluate changes in the clinical presentation of celiac disease in southeastern Wisconsin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 22 publications
9
92
1
4
Order By: Relevance
“…33 Combined emergency and elective cesarean rates increased by 78% between 1990 and 2010 in Scotland. 35 Rising age at diagnosis has been observed in the United Kingdom since the 1960s, 36 increasing to between 7 and 9 years more recently, 8,9,20 which is evident in the current dataset. Children presenting nonclassically and those identified through targeted screening were significantly older at diagnosis, with these phenotypes becoming more prolific as clinical awareness has improved.…”
Section: Figurementioning
confidence: 58%
See 1 more Smart Citation
“…33 Combined emergency and elective cesarean rates increased by 78% between 1990 and 2010 in Scotland. 35 Rising age at diagnosis has been observed in the United Kingdom since the 1960s, 36 increasing to between 7 and 9 years more recently, 8,9,20 which is evident in the current dataset. Children presenting nonclassically and those identified through targeted screening were significantly older at diagnosis, with these phenotypes becoming more prolific as clinical awareness has improved.…”
Section: Figurementioning
confidence: 58%
“…[6][7][8][9][10] A number of articles also report that a greater proportion of children in more recent years are diagnosed through targeted screening and experience fewer GI symptoms. [7][8][9] However, no report has calculated the incidence of cases diagnosed over time because of a lower threshold to test or on the basis of the well-established classic presentation. Analyses performed on such robust data will help to determine whether a rise in incidence can entirely be attributed to a heightened clinical awareness or whether a true rise is evident.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…40 Earlier studies have yielded inconsistent results on the correlation between clinical picture and histological findings in celiac disease. 20,[41][42][43] Apart from differences in study designs these discrepancies might be at least partly explained by differences in clinical presentation of the disease between countries. During recent decades, studies from many developed countries have reported that the severity of celiac disease is becoming milder even in the subgroup of patients suffering from classical gastrointestinal symptoms, 44,45 which may contribute to the increasing similarity between clinically and screen-detected children.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from a North American CD clinic, 71.4% of children with diabetes reported no gastrointestinal symptoms at the time of a positive screen 74 . Some patients are overweight or obese at diagnosis; 11.2% of children with CD had a BMI greater than the 90th percentile in a recent US study 72 .…”
Section: Evaluation For Celiac Disease In Diabetes Mellitus Type 1 Pamentioning
confidence: 97%